Shrinking Remittances in Central Asian Economy - Mirzali, Farid (2023)
This thesis investigates the intricate relationship between the Russian economy and the economies of Uzbekistan and Tajikistan within the context of remittance flows, recognizing these nations as highly reliant on such inflows in the Central Asian region. The primary focus is to analyze the impact of diverse challenges within the Russian economic landscape on remittance patterns in Uzbekistan and Tajikistan. Using the Gravity model as an analytical framework, this research quantifies the extent to which macroeconomic shifts in Russia influence the outflow of remittances to Central Asian countries, taking into consideration countries of Caucasus as well. Beyond this, the study extends its scope to explore the potential influences of multifaceted factors, including the effects of the COVID-19 outbreak, oil price shocks, and the subsequent ramifications of sanctions on the dynamics of remittances between Russia and the Central Asian economies. The thesis aims to provide comprehensive analytical evidence revealing the interconnectedness of these economies and their implications on remittance flows. By dissecting the impact of these various economic and geopolitical factors, this research endeavors to offer valuable insights for further studies in this domain.